PENGARUH DIGITAL MARKETING DAN DIGITAL PAYMENT TERHADAP PENJUALAN UMKM KABUPATEN BANDUNG BARAT DENGAN DYNAMIC CAPABILITIES SEBAGAI VARIABEL INTERVENING - Dini Hidayanti; Nur Jamilah (Jurnal Administrasi Bisnis (JUBIS), 2026)
This study aims to analyze the influence of Digital Marketing and Digital Payment on MSME sales performance in West Bandung Regency, with Dynamic Capabilities as a mediating variable. Using a quantitative approach, data were collected from 100 MSME respondents who met the minimum business operation criterion of at least two years. Data analysis using PLS-SEM revealed that Digital Marketing and Digital Payment have a positive and significant effect on both Dynamic Capabilities and sales performance. However, Dynamic Capabilities were found to have no significant effect on sales performance and were not proven to mediate the relationship between the independent variables and sales. These findings imply that improvements in MSME sales performance are more directly influenced by the implementation of digital technologies rather than through the internal development of organizational dynamic capabilities.